An improved method for efficient controlling of the dynamic voltage restorer to enhance the power quality in the distribution system - Ali Basim Mohammed; Mohd Aifaa Mohd Ariff; Sofia Najwa Ramli (Institute of Advanced Engineering and Science, 2020)
This paper represents a low complexity of the DVR controller by using a robust differentiator named as approximate classical sliding mode differentiator (ACSMD) to overcome the drawback of the linear differentiator. Additionally, utilize a nonlinear sliding variable named arctan function (sigmoid function) in order to keep the magnitude of the load voltage approximately 1pu, the THD at the standard level, improve the robustness property and maintain the steady-state error within a small bound. The most important issues of the power system network are power quality, the major problems of power quality are voltage sag/swell and harmonics which cause tripping or malfunctioning of the equipment. This paper gives an economic and effective solution by utilizing the dynamic voltage restorer to protect the sensitive loads from the disturbances that happened in the system such as voltage sag/swell and harmonics. The proposed system of the DVR is investigated by utilizing MATLAB/Simulink to enhance the disturbances when it occurs in a distribution system. The presents DVR model is evaluated by utilizing some of the popular voltage sag indices.